If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -1 = 1 + 4x Reorder the terms: -1 + 10x = 1 + 4x Solving -1 + 10x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 10x + -4x = 1 + 4x + -4x Combine like terms: 10x + -4x = 6x -1 + 6x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 6x = 1 + 0 -1 + 6x = 1 Add '1' to each side of the equation. -1 + 1 + 6x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = 1 + 1 6x = 1 + 1 Combine like terms: 1 + 1 = 2 6x = 2 Divide each side by '6'. x = 0.3333333333 Simplifying x = 0.3333333333
| 7-5/3=1 | | 16=3x-5(-8x+14) | | y/6-3=-11 | | 10x^2+0-76=0 | | 3/2y-3x=3 | | 13=w-14/2 | | X+2(x+3)-1=1.5(4x+28) | | 9x1/3squared | | 3v+2=32 | | 9*k-4=6*9+k | | 1/2x•5=75 | | 50-2n= | | 5=5(4n-1)/3 | | 2x*x*x=126 | | (W+8)(w-3)= | | -3x-4y=23x+3y=-3 | | 5x-4=2x+44 | | 9-2(7-8w)=11w | | square(3x-2)+3=4x | | 2=3x-5x^3 | | 6/19=x-12 | | y=3x-5x^3 | | 4/cos55 | | -2(-d-9)=3d+14 | | 3/4n= | | 4(x+2)=5(x-38.4) | | 25x-16=235 | | 25h(63)-7w=800 | | (10v-5)*(-1/5) | | 13=-4+x | | 3x-9+2x=2(x+3) | | -19-m=8(1+m) |